2019
DOI: 10.1080/09640568.2018.1560003
|View full text |Cite
|
Sign up to set email alerts
|

A spatial analysis of air pollution and environmental inequality in Beijing, 2000–2010

Abstract: Whilst air pollution is a major problem in China, little is known about how it is distributed socially and how such distributions are changing over time. We use population census and air quality data for 2000 and 2010 to explore socio-spatial and temporal inequalities in air pollution for Beijing. We find that clear environmental inequalities exist with respect to measures of social disadvantage, such as hukou migrant status, very young children (aged 0-4 years), and the elderly (aged ≥ 65 years). Our temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Studies have documented and quantified racial/ ethnic inequity in the level of exposure to fine PM and consumption of goods and services in the United States (Tessum et al 2019). Several studies in other countries such as China have shown that people with lower socio-economic status (SES) are at higher risk of exposure to air pollution (Li et al 2018, Ma et al 2019. Other studies found that risk of PM differs across regions and populations due to demographic or socioeconomic factors .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have documented and quantified racial/ ethnic inequity in the level of exposure to fine PM and consumption of goods and services in the United States (Tessum et al 2019). Several studies in other countries such as China have shown that people with lower socio-economic status (SES) are at higher risk of exposure to air pollution (Li et al 2018, Ma et al 2019. Other studies found that risk of PM differs across regions and populations due to demographic or socioeconomic factors .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study found that migrant older people have less access to various well-being resources than urban residents due to residential segregation caused by Hukou’s institutional constraints [ 62 ]. Concerns about socio-spatial inequalities are echoed in an air pollution study that reveals migrant groups bore a disproportionate share of Beijing’s declining air quality from 2000 to 2010 [ 63 ]. As the burden of commuting differs between employees with and without a local Hukou, institutional discrimination arises; the former may exercise their right in terms of accommodation provided by the work unit.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Crow-der and Downey (2010) interpreted the attenuation of the estimated relationship between pollution and Asian population upon addition of education and family income 'controls' as evidence that lower levels of pollution experienced by Asians were "largely attributable to Asian's slightly greater socioeconomic resources". Some authors more explicitly interpret multivariate linear model parameter estimates as associations "independent" of controlled effects (Grineski et al, 2007;Pearce et al, 2006) or as ceteris paribus associations (Laurian, 2008;Ma et al, 2019). Others are more conservative, instead characterizing estimates as simple associations or stating that a positive estimate implied that the dependent variable increases with the independent variable (Rooney et al, 2012).…”
Section: On Multivariate Regressionmentioning
confidence: 99%